التهاب الجيب الوتدي الفطري المنعزل - العلوني, فايز (Latakia University Journal -Medical Sciences Series, 2013)
لقد تأكدنا من خلال مراجعة الأدب الطبي من ندرة مصادفة إصابة الجيب الوتدي وحيد الجانب المعزول بالرشاشيات السود, ومن أن التشخيص غالباً مايكون صعباً وخاصة قبل تطور وسائل التصوير الشعاعي لأن المريض يراجع عادة بأعراض غير وصفية مثل الصداع واضطراب الرؤيا وشلول غير مفسرة في الأعصاب القحفية. قدمنا في هذه الدراسة حالة سريرية لالتهاب فطري بالرشاشيات معزول في الجيب الوتدي الأيسر فقط,عند مريضة تشكو من صداع وشفع, تم التشخيص بمساعدة التصوير الطبقي المحوري, والرنين المغناطيسي وتمت المعالجة بالتنظير وبمساعدة جهاز الملاحة وكانت النتيجة زوال الأعراض تماماً. From literature review concerning diagnosis and management of isolated sphenoid fungal sinusitis we found that this isolated lesion is extremely rare especially in immunocompetent patients; it is frequently difficult to diagnose, as patients present with nonspecific symptoms such as headach, visual disturbance and cranial nerve palsies. Diagnosis of the disease is typically not made until advanced imaging has been developed. We presented a case of isolated fungal sinusitis of left sphenoid sinus with headach and diplopia, treated by endoscopic sphenoidotomy with the help of the navigation system, after which recovery was full.